Synthesis, structure and electromagnetic properties of FeCoAl/C nanocomposites - Dmitriy G. Muratov (Pensoft Publishers, 2021)
Magnetic nanoparticles play an important role in rapidly developing advanced branches of science and industry, e.g. fabrication of magnetic storage media, synthesis of ferromagnetic liquids, medicine and chemistry. One problem faced in the usage of magnetic nanoparticles is their high chemical activity leading to oxidation in air and agglomeration. The chemical activity of magnetic nanoparticles stems from the contribution of their large specific surface to volume ratio. Carbon coating of nanoparticles reduces the interaction between nanoparticles. FeCoAl/C metal-carbon nanocomposites have been synthesized using IR pyrolysis of polymer/metal salt precursors. The effect of synthesis temperature (IR heating) in the range from 500 to 700 °C on the structure and composition of the nanomaterials has been studied. We show that the forming particles are the FeCoAl ternary solid solution with a FeCo based bcc lattice. An increase in the synthesis temperature from 500 to 700 °C leads to an increase in the coherent scattering region of three-component nanoparticles from 5 to 19 nm. An increase in the aluminum content from 20 to 30% relative to Fe and Co results in an increase in the size of the nanoparticles to 15 nm but this also entails the formation of a Co based solid solution having an fcc lattice. An increase in the nanocomposite synthesis temperature and a growth of the relative Al content as a result of a more complete carbonization and the structure-building effect of metals reduce the degree of amorphousness of the nanocomposite carbon matrix and lead to the formation of graphite-like phase crystallites having an ordered structure. The effect of synthesis temperature and relative content of metals on the electromagnetic properties (complex permittivity and permeability) of the synthesized nanocomposites has been studied. Synthesis conditions affect the radio absorption properties of the nanocomposites, e.g. reflection loss (RL) in the 3–13 GHz range.